Trueperella pyogenes as an abortion cause in a cow-case report Trueperella pyogenes como causa de aborto em uma vaca-relato de caso - Costa L.S.* (2019)
© 2019, Universidade Federal de Minas Gerais.Trueperella pyogenes is an opportunistic bacterium associated with mastitis, metritis and occasional abortion in bovines. Here we report an uncommon case of abortion by T. pyogenes in a cow. An aborted female Brahman bovine fetus, at 8 months of gestational age was submitted for anatomopathological examination and complementary diagnostic tests. Macroscopic findings at necropsy included large amounts of free serum-blood fluid and moderate fibrin deposition covering both the visceral pleura and pericardial sack. The lungs were diffusely reddened and markedly consolidated, showing widespread smaller than 1cm, hard, white nodules. Necrosuppurative pneumonia, fibrinopurulent pleuritis, and purulent placentitis were the main histopathologic alterations observed. Trueperella pyogenes was isolated from liver, lungs, abomasa contents and placental samples. All tissue samples were PCR-negative for Neospora caninum, Toxoplasma gondii and bovine viral diarrhea virus (BVDV). Although T. pyogenes is often involved in suppurative bronchopneumonia and abscesses formation, macro and microscopic lesions in the present report were compatible with those commonly attributed to Brucella abortus fetal infections. Trueperella pyogenes is an important bovine pathogen with a neglected zoonotic potential being responsible for infections that can mimic other diseases' typical presentations.